Ylidenemalononitrile enamine-coated media as fluorescent "turn-on" probes for volatile primary amines. Issue 4 (2nd February 2017) - Longstreet, Ashley R.; Chandler, Rebecca R.; Banerjee, Tanmay; Zane Miller, L.; Hanson, Kenneth; Tyler McQuade, D.
Abstract : Two ylidenemalononitrile enamines, adsorbed to various media, undergo a cyclization reaction with primary amine vapors resulting in a fluorometric and colorimetric response. Abstract : Two ylidenemalononitrile enamines, adsorbed to various media, undergo a cyclization reaction with primary amine vapors resulting in a fluorometric and colorimetric response. After determining the media with the fastest response rate for emission "turn-on" to be aluminum oxide activated neutral (AON), we further demonstrate the sensitivity (propylamine concentrations as low as 200 ppm are detected) and selectivity to various analytes including amines, methanol, and ethanethiol. Lastly, as an alternative means of detection, the colorimetric response dye on glass filter paper was shown to detect propylamine concentrations as low as 29 ppm.